Learning History In America : Schools, Cultures, and Politics - Barney, William L.; Reid, Donald; Kramer, Lloyd S. (Book collections on Project MUSE., 1994)
As it extends recent discussions about multiculturalism into the sphere of contemporary historical understanding, this book sets out explicitly to explore the practical and theoretical implications of these discussions for people who learn and teach history in the United States.